Free cash flow and corporate profitability in emerging economies: Empirical evidence from Vietnam - Nguyễn, Thanh Hồng Ân (2022)
This paper examined the relationship between free cash flow and corporate profitability of Vietnamese listed firms. Based on the agency theory of free cash flow, several previous studies proposed a negative relationship between free cash flow and corporate profitability. In this study, we argue that the presence of information asymmetry in the financial market of developing economies may limit access to external sources of finance. Thus, free cash flow may serve as a cheaper alternative source of finance. This benefit may reduce, nullify, or even outweigh the agency cost caused by excess free cash flow. The empirical analysis results based on a sample of 208 Vietnamese listed nonfinancial firms in the period from 2012 to 2016 showed that free cash flow seems to have a positive effect on the corporate profitability of Vietnamese listed firms.